The ship in the window - Jonker, Travis; Cordell, Matthew, 1975- (New York : Viking, 2024)
Mabel, a mouse with dreams of being a sea captain, embarks on a daring adventure with a model ship, bringing the man who built it and his son closer together.
K-3
AD560L
Keywords: Mice -- Juvenile fiction; Ship models -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Mice -- Fiction; Ship models -- Fiction; Fathers and sons -- Fiction; Animal fiction; Models and model making -- Juvenile fiction